2020
DOI: 10.1155/2020/8308616
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin Mitigates Total Body Irradiation-Induced Hematopoietic Injury in Mice

Abstract: Sitagliptin, an inhibitor of the dipeptidyl peptidase IV (DPP4), has been implicated in the regulation of type 2 diabetes. However, the role and mechanism of sitagliptin administration in total body irradiation (TBI)- induced hematopoietic cells injury are unclear. In this study, we demonstrated that sitagliptin had therapeutic effects on hematopoietic damage, which protected mice from 7.5 Gy TBI-induced death, increased the numbers and colony formation ability of hematopoietic cells. These therapeutic effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Accumulated evidence suggests that Sitagliptin not only regulates blood glucose but also has pleiotropic effects of anti-inflammatory, antioxidant, and antiapoptotic. Sitagliptin has been reported to have therapeutic effects on radiation-induced hematopoietic damage [ 33 ]. In our study, we found that once-daily treatment with Sitagliptin starting 1 hour before radiotherapy could protect the mice from death and weight loss induced by WAI.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated evidence suggests that Sitagliptin not only regulates blood glucose but also has pleiotropic effects of anti-inflammatory, antioxidant, and antiapoptotic. Sitagliptin has been reported to have therapeutic effects on radiation-induced hematopoietic damage [ 33 ]. In our study, we found that once-daily treatment with Sitagliptin starting 1 hour before radiotherapy could protect the mice from death and weight loss induced by WAI.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation‐induced suppression of haematopoiesis and immune function has been one of the most life‐threatening consequences of radiation exposure 26 . In order to assess the influence of radiation on the haematopoietic system, TBI 4 Gy as a sublethal dose was selected as the challenge of radiation exposure 27,28 . Our present data demonstrated that lymphocytes maintain an impair level after 9 days TBI 4 Gy, due to the irreversibly damaged haematopoietic stem cells no longer produce mature blood cells.…”
Section: Discussionmentioning
confidence: 64%